Analysis of The English Open Compound Words - Fadlan Ihsan; Raflis Raflis (Jurnal Ilmiah Pendidikan Scholastic, 2019)
Compound words are one of the elements found in the field of morphology. Where the morphology is the study of morphemes, and morphemes are elements of language that have meaning and contribute to support meaning. The morphology field will involve two elements, namely the free element and the bound element. The problem in this study is to analyze the compound word found in the Jakarta post. The word compound which is discussed is the compound word that is open (separate word writing).This research is a type of research belonging to the field of linguistics. This study also uses Qualitative Descriptive research methods. This research method refers to the form of the word. In addition, this research also uses library research or library research. Putaka's research only discusses the data that has been provided by processing and donating data obtained from data sources by using the basic theory that supports the research. In this study the writer took data sources from one edition of the Jakarta Post. All data needed comes from the data source.The initial step used by the writer is to extract raw data taken from the source. After all the raw data is collected, the author will classify the data in several groups. Since the writer only discusses three topic issues, the information is in accordance with the problem. The first problem is the form of the compound word separated which is found in the Jakarta Post Newspaper. Second is what is the meaning of the compound words before and after combined. And the last is the rule that is owned by the compound. Based on this research, the writer find the uniqueness that results from a separate word combination. Among them is if one word is combined with another word it will have a different meaning. Based on this research the author understands in depth about the separate word combination.